First reported Tannerella forsythia infection in a patient with extensive bronchiectasis: a case report - Congli Fu; Yilan Sun; Chun Chen (Frontiers in Medicine)
Tannerella forsythia infection was common in oral diseases but less reported in lung diseases. This report presents a patient with bronchiectasis who was infected by Tannerella forsythia and subsequently hospitalized with symptoms including fever, progressive cough, sputum production, and shortness of breath. A chest computed tomography (CT) scan revealed multiple bilateral pulmonary bronchiectasis with signs of infection. Metagenomic next-generation sequencing (mNGS) of the bronchoalveolar lavage fluid primarily detected Tannerella forsythia. Treatment with Piperacillin-tazobactam and ornidazole resulted in a favorable outcome. This case first reported a patient with extensive bronchiectasis infected by Tannerella forsythia and provided an effective treatment.